Patient-reported outcomes (PRO) focused on adverse events (PRO-AEs) in adjuvant and metastatic breast cancer: clinical and translational implications - Stefanovic, Stefan; Wallwiener, Markus; Domschke, Christoph; Schütz, Florian; Sohn, Christof; Schneeweiss, Andreas (Supportive care in cancer, 2017)
Purpose: The capture of adequate treatment outcomes and quality of life (QOL) of advanced breast cancer patients in clinical routine represents a great challenge. Patient-reported outcomes (PROs) are data elements directly reported by patients about experiences with care, including symptoms, functional status, or quality of life. There is growing interest in the medical community for the evaluation and implementation of PROs of adverse events (PRO-AEs). Recent interest in PROs in health care has evolved in the context of patient centeredness. Our primary objective was to identify trials that had implemented PRO-AEs in the breast cancer treatment setting, thereby demonstrating its feasibility. We aimed to identify published studies that used patient reports to assess AEs during and after breast cancer treatment, to identify clinician underreported and modifiable AEs that are important to patients, and to analyze the feasibility and usefulness of PRO instrument implementation in everyday oncological practice with special attention given to electronic-based PRO instruments. Methods: We conducted a systematic search of PubMed for studies that used PRO instruments to assess AEs of breast cancer treatment in the metastatic and adjuvant settings. Two authors independently reviewed the search results and decided which studies fully met the predefined inclusion criteria.ResultsThe search yielded 606 publications. The two reviewers found that 9 studies met the inclusion criteria. Three AEs were identified as important to patients but inadequately reported by health care providers, namely hot flushes, vaginal dryness, and weight gain. Conclusions: PROs and PRO-AEs are the consequence of contemporary concepts of patient-centered medicine and the growing feasibility, utility, and implications of collecting data using modern technology. Furthermore, the willingness of patients to utilize innovative applications for their own health has been increasing in parallel to the enhanced impact of the World Wide Web. Especially, the coverage of the metastatic situation promises numerous findings on the structure and quality of health care, enabling implementation of individually tailored interventions. Remote electronic self-reporting (i.e., home reporting) is feasible and is associated with high compliance levels.
First online: 17 October 2016
Gesehen am 14.09.2018